Mo modified Co3O4 nanosheets array by a rapid quenching strategy for efficient oxygen evolution electrocatalysis - Yang, Jiangping; Zhang, Zhe; Sun, Siyuan; Wang, Cheng (Frontiers in Materials, 2022)
Transition metal oxides (TMO) as electrocatalysts for oxygen evolution reaction (OER) have shown great potential to overstep noble-metal-based catalysts but low intrinsic activity and limited active site. Herein, we developed a quenching rapidly strategy to synthesize Mo-modified Co3O4 nanosheet array as advanced catalysts. Typically, the Co3O4 electrode modified by Mo cations (Mo-Co3O4) possesses superior activity and reaction kinetics, with an overpotential of only 341 mV to drive the current density of 100 mA cm-2 and a Tafel slope of 69.0 mV dec-1, due to the modification-induced synergistic effect by forming high-valence Co sites. Considering the ingenious regulation without any obvious agglomeration and nucleation growth under annealing, this work can be further extended to design other advanced functional materials by facile surface modification for potential applications.